Threshold reduction of stimulated Brillouin scattering in photonic crystal fiber - Shee Y.G.; Mahdi M.A.; Al-Mansoori M.H.; Ismail A.; Hambali N.A.M.A.; Zamzuri A.K.; Mohamad R.; Yaakob S. (2023)
A simple configuration for the reduction of stimulated Brillouin scattering threshold in photonic crystal fiber is presented. The threshold reduction is contributed by the bidirectional pumping scheme through the reflection of transmitted Brillouin pump back to the gain medium. The pump recycling scheme has greatly reduced the Brillouin threshold of a 200-m long of photonic crystal fiber from 50 to 30 mW of Brillouin pump power. 2009 Pleiades Publishing, Ltd.